2013
DOI: 10.1002/2013gl058307
|View full text |Cite
|
Sign up to set email alerts
|

Postmidnight bubbles and scintillations in the quiet‐time June solstice

Abstract: [1] While the mechanism for producing plasma irregularities in the dusk sector is believed to be fairly well understood, the cause of the formation of irregularities and bubbles during the postmidnight sector is still unknown, especially for magnetically quiet periods. This paper presents a case study of the strong postmidnight bubbles that often occur during magnetically quiet periods primarily in June solstice, along with a 4 year (2009)(2010)(2011)(2012) statistical study that shows strong occurrence peak d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
110
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 96 publications
(120 citation statements)
references
References 22 publications
9
110
1
Order By: Relevance
“…This peak located between 21 and 22 LT during the quiet times for all seasons and during the disturbed times for the March and September equinox seasons (Su et al 2006). The post-midnight equatorial plasma irregularities are relatively rare events; more observations of the post-midnight plasma bubbles and longitudinally broad depletions (trenches) have been reported recently with the C/NOFS satellite (e.g., Burke et al 2009;Yizengaw et al 2013). Thus, the temporal interval of 20-23 LT should provide a major contribution to the occurrence rate probability of equatorial irregularities.…”
Section: Resultsmentioning
confidence: 79%
“…This peak located between 21 and 22 LT during the quiet times for all seasons and during the disturbed times for the March and September equinox seasons (Su et al 2006). The post-midnight equatorial plasma irregularities are relatively rare events; more observations of the post-midnight plasma bubbles and longitudinally broad depletions (trenches) have been reported recently with the C/NOFS satellite (e.g., Burke et al 2009;Yizengaw et al 2013). Thus, the temporal interval of 20-23 LT should provide a major contribution to the occurrence rate probability of equatorial irregularities.…”
Section: Resultsmentioning
confidence: 79%
“…The figure clearly shows activity in all seasons and strong bubbles/irregularities in the African sector compared to other longitudinal sectors. Recently, Yizengaw et al (2013b) reported significantly strong bubbles in the African sector during post-midnight local time under magnetically quiet conditions in June solstice. The question is if the drift is weaker in the African sector, what causes these strong bubbles that have been observed in the African sector almost throughout the night and during all seasons?…”
Section: Discussionmentioning
confidence: 99%
“…Since these irregularities often exist inside plasma bubbles, they have long been regarded as indications for EPBs (Abdu et al, 2003;Basu et al, 1980;Demyanov et al, 2012;Lühr et al, 2014;Ma & Maruyama, 2006;Park et al, 2005;Rama Rao et al, 2009;Rodrigues et al, 2009;Xiong et al, 2016;Yizengaw et al, 2013;Yokoyama et al, 2007). Since these irregularities often exist inside plasma bubbles, they have long been regarded as indications for EPBs (Abdu et al, 2003;Basu et al, 1980;Demyanov et al, 2012;Lühr et al, 2014;Ma & Maruyama, 2006;Park et al, 2005;Rama Rao et al, 2009;Rodrigues et al, 2009;Xiong et al, 2016;Yizengaw et al, 2013;Yokoyama et al, 2007).…”
Section: Data and Analysis Methodsmentioning
confidence: 99%